A Fete of topology : papers dedicated to Itiro Tamura - Tamura, Ichiro, 1926-1991; Matsumoto, Yukio, 1944-; Mizutani, T. (Tadayoshi), 1945-; Morita, Shigeyuki, 1946- (Academic Press, 1988)
A Fete of Topology.